HELPING STUDENTS OF ARABIC DEPARTMENT OR PESANTREN LEARN THE ENGLISH DERIVATION - Handoko, Handoko (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2015)
Presenting the comparative description of English derivation and Arabic derivatives, this paper is intentionally purposed to help students to understand the English derivation. Most of students, especially the students of Arabic department or students who are familiar with Arabic as they have learned before, regard that English language is difficult to learn. To solve this problem, the writer provides a comparative study by using Arabic as another language that he knows. This paper constitutes an exploratory study of derivatives in both English and Arabic, provides procedures in teaching English derivation to the students who have basic knowledge in Arabic, and then gives reflection and conclusion.